2003
DOI: 10.1017/s014271640300016x
|View full text |Cite
|
Sign up to set email alerts
|

English word recognition and word integration skills of native Arabic- and Japanese-speaking learners of English as a second language

Abstract: This study investigated the effects of first language word-level reading skills on the development of English as a second language (ESL) word-level reading skills. A crosslinguistic analysis indicates that native Arabic and Japanese speakers are likely to encounter different types of ESL word-level reading difficulties. Specifically, native Arab speakers are likely to exhibit difficulties with prelexical ESL word recognition processes, whereas native Japanese speakers are likely to exhibit difficulties with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
80
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 94 publications
14
80
0
1
Order By: Relevance
“…The three participants showed some degree of an interactive model of reading with overt dominance of a top-down approach. Fender (2003) supports the findings of the present study. He found that Arab ESL learners would comprehend their reading by means of relating and integrating the meaning of words into the bigger picture.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The three participants showed some degree of an interactive model of reading with overt dominance of a top-down approach. Fender (2003) supports the findings of the present study. He found that Arab ESL learners would comprehend their reading by means of relating and integrating the meaning of words into the bigger picture.…”
Section: Discussionsupporting
confidence: 93%
“…Perry claimed adherence to the framework prescribed by Stanovich (1980) and Carrell (1984), which views reading as an interactive-compensatory process. Abbott (2006) andFender (2003) conducted two comparative studies about Arab ESL learners and their Chinese and Japanese learners' counterparts. They both assert that Arab ESL learners employed a top-down reading approach.…”
mentioning
confidence: 99%
“…Research has also suggested that language-specific differences are related to differences in processing skills and strategies in reading (Akamatsu, 2003;Bang & Zhao, 2007;Chen, 1992;Fender, 2003;Hayes-Harb, 2006;Koda, 1988Koda, , 1989Koda, , 2005Wang & Koda, 2007;Wang, Koda, & Perfetti, 2003). For example, when Koda (1988Koda ( , 1989) compared the cognitive strategies of ESL readers from four L1 orthographic backgrounds, she found that when reading in English, the readers used cognitive strategies developed in their L1.…”
Section: The Effects Of Linguistic Differences On Readingmentioning
confidence: 99%
“…Despite conflicting results regarding which of these two categories contributes most to reading comprehension, the common conclusion from studies of the relationship between strategy use and reading ability is that reading comprehension is more likely to occur when people use strategies both actively and flexibly during reading given the nature of the context (Anderson; Barnett, 1988;Block, 1986Block, , 1992Phakiti;Purpura;Sarig, 1987;Schueller;Young & Oxford). Nonetheless, a clearer understanding of reading strategy use is necessary to help language-learners discover when, where, and how to use strategies effectively.Although some reading strategy training studies (Barnett, 1988;Schueller, 2004) suggest that strategy training improves comprehension, most strategy training programs are generic in nature in the sense that they do not address research that suggests that learners from diverse cultural, linguistic, and educational backgrounds tend to rely on varied reading strategies and/or varied word recognition strategies when attempting English academic reading tasks (Akamatsu, 2003;Bang & Zhao, 2007;Chen, 1992;Fender, 2003;Koda, 1988Koda, , 2005Koda, , 2007Parry, 1996). Before successful reading strategy training programs specifically designed for language-learners from a variety of linguistic/cultural groups can be developed, researchers need to explore the differences in strategy use that exist between linguistic/cultural groups.…”
mentioning
confidence: 99%
“…Abbot (2004) found Arabic L1 students tended to score higher on questions requiring contextual, global 'top-down' strategies than Chinese readers, who outdid the Arabic readers on word analysis strategies. Similarly, Fender (2003) found Arabic learners used meaning and context more than Japanese learners. One theory as to why top-down processing seems to be so heavily relied on by Arabic L1 readers is that when Arabic is written in its usual, de-vowelled form, the large number of identical-looking words cannot be discriminated without referring to sentence context to know which word is intended (Abu- Rabia, 1997Rabia, , 2001).…”
Section: Arabic L1 Esl Studentsmentioning
confidence: 94%